Abstracts from the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) Trainees Symposium. Issue 3 (September 2013) - Unknown
On July 12, 2013, more than 30 fellows and trainees from around the world presented abstracts at the Trainees Symposium at the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) annual meeting in Toronto, Canada. The symposium was developed as an opportunity for trainees and fellows in rheumatology and dermatology to develop their research skills through presentation and discussion of their work. The topics of the poster presentations ranged widely, reflecting many aspects of GRAPPA's work streams. Subjects included comorbidities, nail disease, screening tools, incidence and prevalence studies, and translational research. Before the meeting, senior GRAPPA members ranked the abstracts, and the top six were invited to present their findings orally with a 15-minute slide presentation. The others were invited to speak for five to seven minutes from posters based on their findings. This year, the six selected to give oral presentations were Muhammad Haroon (Ireland), Will Tillett (UK), Mary Ann Johnson (U.S.A.), Agnes Szentpetery (Ireland), Amir Hadaad (Canada) and DoQuyen Huynh (U.S.A.). Professor Christopher Ritchlin, M.D., M.P.H., of the University of Rochester School of Medicine (New York) founded the GRAPPA Trainees Symposium in 2008. It has been a popular addition to the GRAPPA annual meeting ever since, with 15 trainees participating in 2008, 19 in 2009 and 31 abstracts submitted in 2013. Here we present a selection of the abstracts submitted by these trainees and fellows in 2013.